Dry, Sarah. (2014). The Newton papers: the strange and true odyssey of Isaac Newton’s manuscripts, Oxford University Press. ISBN: 978-0-19-995104-8: El Newton que no conocíamos - Arsioli Moura, Breno (Prometeica - Revista de Filosofía y Ciencias, 2019)
Não há.